A Protection-Motivation Perspective to Explain Intention to Use and Continue to Use Mobile Warning Systems - Diana Fischer-Preßler; Dario Bonaretti; Kai Fischbach (Business & Information Systems Engineering, 2021)
Mobile emergency warning apps are essential for effective emergency communication – of course, provided the population intends to use them. Drawing on protection motivation theory, the study validated a psychometric model to explain what motivates individuals to install a warning app for the first time and to keep using it over time. Multi-group covariance-based structural equation modeling was used to model the answers to a survey that measured the drivers of intention to begin using or intention to continue using a warning app. The model shows that, for both non-users and users, trust, social influence, and response efficacy positively and maladaptive rewards negatively affect intention to use and intention to continue use warning apps. However, perceived vulnerability influences only intention to use, whereas response cost and self-efficacy affect continued use intention. Hence, this study enhances the theoretical understanding of technology-enabled protection behaviors and provides practitioners with a list of factors to consider for pushing the adoption and continued use of emergency warning applications.
Keywords: 000; Protection motivation theory; Emergency notification; Disaster; Warning app; Use intention; Continuance; Multi-group analysis